The Effect of Managerial Ownership and Executive Characteristics on Tax Planning with Corporate Governance as a Moderating Variable - Chandrika Anggraini Puspitasari; Bani Binekas (Amkop Management Accounting Review (AMAR), 2026)
This research examines whether managerial ownership and executive behavior influence corporate tax planning practices, with corporate governance as a moderating factor over the 2020-2024. The study is motivated by variations in Effective Tax Rates among companies, which indicate differences in tax planning strategies. The implementation of tax planning serves as a legal strategy to minimize the tax burdens. However, overly aggressive tax planning can pose a risk of loss to the company. A quantitative design as employed using purpose sampling and obtaining 18 food and beverage manufacturing companies with a total of 90 observational data. Hypotheses were tested with multiple linear regression and Moderatation Regression Analysis (MRA). The results showed that managerial ownership yields not significantly affect on tax planning, whereas executive characteristics have a negative effect on tax planning. Simultaneously, both variables have a significant effect on tax planning, and corporate governance was unable to moderate each variable effect indivually, but successfully moderated the overall effect of both variables on tax planning.